2014
DOI: 10.1177/0300060514543038
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial performance is impaired in patients with branch retinal vein occlusion

Abstract: Myocardial performance is decreased in patients with BRVO, independent of whether or not they have hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
7
0
4
Order By: Relevance
“…This finding correlates with the study by Kaderli et al that states that myocardial function is impaired in patients with BRVO. 13 We therefore speculate that poor presenting visual acuity in RVO is a consequence of relative retinal ischemia attributable to carotid narrowing evidenced by association with higher IC PSV and IC to CC PSV ratio. In addition, the TMV in patients with CRVO was higher in those with larger ventricular diameter at the end of systole.…”
Section: Quantitative Carotid Doppler and Cardiac Echography In Rvomentioning
confidence: 77%
See 2 more Smart Citations
“…This finding correlates with the study by Kaderli et al that states that myocardial function is impaired in patients with BRVO. 13 We therefore speculate that poor presenting visual acuity in RVO is a consequence of relative retinal ischemia attributable to carotid narrowing evidenced by association with higher IC PSV and IC to CC PSV ratio. In addition, the TMV in patients with CRVO was higher in those with larger ventricular diameter at the end of systole.…”
Section: Quantitative Carotid Doppler and Cardiac Echography In Rvomentioning
confidence: 77%
“…1,11 Association of retinal vascular changes with increased risk of cardiovascular dysfunction has been brought out in other studies as well. 5,12,13,14 Song and colleagues have shown that retinal vascular analysis has good predictive value in identifying atherosclerosis of the carotid artery in asymptomatic patients. 15 The severity of coronary disease may also be estimated by retinal vascular analysis, and myocardial performance is known to be decreased in patients with BRVO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Although the state of endothelial dysfunction is not known in patients with RVO, it has been reported that the ejection fraction is signi cantly lower, and suboptimal cardiac functions are associated with larger systolic diameters in cardiac structures. 16 It has been reported that patients with BRVO have myocardial dysfunction, and these patients may need monitoring in terms of CAD 17 . It has been shown that the severity of coronary diseases and myocardial performance can be estimated by a retinal vascular analysis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although the state of endothelial dysfunction is not known in patients with RVO, it has been reported that the ejection fraction is signi cantly lower, and suboptimal cardiac functions are associated with larger systolic diameters in cardiac structures. 16 It has been reported that patients with BRVO have myocardial dysfunction, and these patients may need monitoring in terms of CAD 17 . It has been shown that the severity of coronary diseases and myocardial performance can be estimated by a retinal vascular analysis.…”
Section: Discussionmentioning
confidence: 99%